PEMERTAHANAN BAHASA DAERAH PADA KAUM EKSPATRIAT INDONESIA DI KOREA SELATAN - Sonezza Ladyanna; Kim Jang Gyem (Puitika, 2019)
Good cooperation relationship between Indonesia and South Korea gives high impact on the migration from Indonesia to South Korea temporarily or permanently which affect the usage of the language by the user or referred as Indonesian expatriates in South Korea. In this article, the usage of languages, language shift, and language retention of the Indonesian expatriates in South Korea are described. The method used in this study is a qualitative method. Data collected by listening to two different media, namely interviews and social networking Facebook. The research subjects were Indonesian expatriates in South Korea, such as workers (TKI-Indonesian Workers), students, and intermarrying Indonesia-Korea families in Korea. The object of this study is the usage of mother tounge, then analyzed by using qualitative methods through sociolinguistic theory and reported descriptively. The results showed two groups of language usage, multilingual and monolingual groups. In the case of migrants or expatriates who are part of intermarrying families, there are three models of language retention. The first model, there is retention of mother tounge (b1) in addition to the usage of the Korean language (b2), and the Indonesian as the third language (b3). All three languages are used according to the situation and condition. The local language retention was found in the second model (b1 without Indonesian language, so using the mother tounge and Korean languages only. In the last model, the speaker who is a mother didn’t teach the mother tounge to their children. She tends to be monolingual, only the Korean language.Keywords: retention of mother tounge, expatriates, South Korea